PERIODONTAL ESTETIK: PERAWATAN RESESI GINGIVA (TINJAUAN PUSTAKA) - Nir Etriyani; Hasanuddin Thahir (Universitas Baiturrahmah, 2021)
Introduction: Gingival recession represents a clinical condition in adults frequently encountered. Gingival recession is the main complaint of patients who come to the dentist due to an unsatisfactory aesthetic problem. Handling this condition requires action depending on the severity of the case gingival recession. the dentist must know the best treatment for the case. This article purpose to review some literature regarding the treatment means for the gingival recession to achieve an esthetic gingival appearance. Review: Gingival recession is the most common clinical manifestation of all oral diseases. The condition can be corrected by two approaches to gain an aesthetic appearance. The first option is mucogingival surgery or gingival plastic surgery. The second option is gingival replacement with artificial substitutes. Treatment of gingival recession is essential to rectify the esthetic and functional deficiencies of the patient and prevent further periodontal destruction. Gingival recession can be treated with different surgical procedures and the root coverage can be obtained from the surgical approach taken. Conclusion: Increased patient awareness of dental esthetic procedures has increased the demand as well as the responsibility of cosmetic dentistry to have outstanding skill and create pleasing results.